If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 44)(3x + -2) = 0 Reorder the terms: (44 + x)(3x + -2) = 0 Reorder the terms: (44 + x)(-2 + 3x) = 0 Multiply (44 + x) * (-2 + 3x) (44(-2 + 3x) + x(-2 + 3x)) = 0 ((-2 * 44 + 3x * 44) + x(-2 + 3x)) = 0 ((-88 + 132x) + x(-2 + 3x)) = 0 (-88 + 132x + (-2 * x + 3x * x)) = 0 (-88 + 132x + (-2x + 3x2)) = 0 Combine like terms: 132x + -2x = 130x (-88 + 130x + 3x2) = 0 Solving -88 + 130x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (-44 + -1x)(2 + -3x) = 0Subproblem 1
Set the factor '(-44 + -1x)' equal to zero and attempt to solve: Simplifying -44 + -1x = 0 Solving -44 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '44' to each side of the equation. -44 + 44 + -1x = 0 + 44 Combine like terms: -44 + 44 = 0 0 + -1x = 0 + 44 -1x = 0 + 44 Combine like terms: 0 + 44 = 44 -1x = 44 Divide each side by '-1'. x = -44 Simplifying x = -44Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-44, 0.6666666667}
| 5(a+3)=2(a-2) | | 15=-3x+2x+6 | | 5+2x-3x=-6 | | 154-3x=24x+22 | | 14-9x=36-23x | | 9-2x-3x=69 | | -x+6-4x=-14 | | 1+x+6x=64 | | .59x=x-338 | | -(8c+4d)/8c-(8c-11d)/8c | | 6x+12=89-5 | | 12x-64=6x-14 | | 45=6x+4x+5 | | 14x+14=0 | | 5x+6-2x=12 | | .45x=x-5.5 | | 2x+9+5x=16 | | 6x-4=5-2(-3x+5)+15 | | -4+5x+3x=-84 | | 10-9x=205-4x | | 175+550x=35+1680x | | 10x-24=6+4 | | 164-4x=23x+17 | | 62-4x=23x+20 | | 1/2(x+10)=3/4x+2 | | 1.10+8.50x=2.25+2.50x | | (12y+10)=180 | | 12x+19=6x+157 | | (-x)(-2xy)(-3xyz)= | | 4/5x+9-2=15 | | (x^2-4x-5)/(4x^2+4x-120) | | (3/(2y))-7x=4x+1 |